Stay out of the basement - Stine, R. L. (New York : Scholastic, 1992)
With their father conducting strange experiments with plants in the basement, Margaret and Casey begin to investigate and soon discover that their father has begun to resemble a plant.
"An Apple paperback."
4-6
600
600
Accelerated Reader AR
Keywords: Horror tales; Horror fiction